Legal Protection for Consumers in Digital E-Commerce Agreements Based on the Civil Code and Consumer Protection Law - Muhammad Reza Elia Habibullah (Veteran Law Review, 2026)
The digitalization of commercial transactions has significantly transformed the formation and enforcement of agreements between businesses and consumers. This study examines the legal validity of digital contracts in Indonesia under the Civil Code (KUH Perdata), “the Electronic Information and Transactions Law (UU ITE), and Government Regulation No. 71 of 2019”, as well as their implications for consumer protection under the Consumer Protection Law (UUPK). Using a normative juridical and comparative method, the research finds that Indonesia recognizes electronic contracts and electronic signatures as legally binding, yet its regulatory framework remains fragmented and does not fully address key elements of digital consumer protection, such as product conformity, withdrawal rights, and mandatory software updates. A comparison with the Netherlands, a civil law country with a more advanced regulatory structure shows that Dutch law, supported by EU frameworks such as the GDPR and Consumer Rights Directive, provides stronger safeguards, clearer obligations for digital content providers, and more effective mechanisms for dispute resolution. The study concludes that although Indonesia has established a basic legal foundation for digital contracting, further regulatory development is required to respond to risks related to data breaches, online fraud, and cross-border e-commerce. Strengthening institutional capacity and harmonizing digital regulations are essential to enhancing consumer protection in the digital era.